High-level dolutegravir resistance can emerge rapidly from few variants and spread by recombination: implications for integrase strand transfer inhibitor salvage therapy. (1st November 2022) - Huik, Kristi; Hill, Shawn; George, Jomy; Pau, Alice; Kuriakose, Safia; Lange, Camille M.; Dee, Nicola; Stoll, Pamela; Khan, Muhammad; Rehman, Tauseef; Rehm, Catherine A.; Dewar, Robin; et al.
Abstract : The integrase strand transfer inhibitor (INSTI) dolutegravir is commonly used in combination antiretroviral therapy regimens and retains strong potency even with primary resistance mutations to some other INSTIs. Acquisition of accessory mutations to primary mutations results in significant increases in dolutegravir resistance. Previously, we reported that addition of the secondary mutation T97A can result in rapid treatment failure in individuals with INSTI mutations at positions 140 and 148. Here, we conducted a detailed case study of one of these individuals and find that T97A-containing HIV emerged from a large replicating population from only a few (≤4) viral lineages. When combined with primary INSTI resistance mutations, T97A provides a strong selective advantage; the finding that T97A-containing variants spread by replication and recombination, and persisted for months after discontinuing dolutegravir, has important implications as dolutegravir is rolled out worldwide.